Impact of Diabetes on Cardiovascular Disease: An Update - Alessandra Saldanha de Mattos Matheus; Lucianne Righeti Monteiro Tannus; Roberta Arnoldi Cobas; Catia C. Sousa Palma; Carlos Antonio Negrato; Marilia de Brito Gomes (International Journal of Hypertension)
Cardiovascular diseases are the most prevalent cause of morbidity and mortality among patients with type 1 or type 2 diabetes. The proposed mechanisms that can link accelerated atherosclerosis and increased cardiovascular risk in this population are poorly understood. It has been suggested that an association between hyperglycemia and intracellular metabolic changes can result in oxidative stress, low-grade inflammation, and endothelial dysfunction. Recently, epigenetic factors by different types of reactions are known to be responsible for the interaction between genes and environment and for this reason can also account for the association between diabetes and cardiovascular disease. The impact of clinical factors that may coexist with diabetes such as obesity, dyslipidemia, and hypertension are also discussed. Furthermore, evidence that justify screening for subclinical atherosclerosis in asymptomatic patients is controversial and is also matter of this review. The purpose of this paper is to describe the association between poor glycemic control, oxidative stress, markers of insulin resistance, and of low-grade inflammation that have been suggested as putative factors linking diabetes and cardiovascular disease.